Acoustic Characteristics of the Chilean Spanish Vowels Produced by Subjects Resident in the City of Santiago - Díaz A., Susane; Cisternas L., Pamela; López B., Ilse (Revista Chilena de Fonoaudiología, 2015)
<!–[if gte mso 9]> <![endif]–> <!–[if gte mso 9]> Normal 0 21 false false false ES-TRAD JA X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> <!–StartFragment–> The aim of this study was, firstly, to describe the acoustic characteristics of isolated vowels produced by Chilean young people from Santiago, Chile, secondly, to compare the results obtained between men and women and, finally, to compare the data with information collected from Argentinian speakers (Rio de la Plata) and Chilean speakers (Concepción). 117 university students were selected for this study. Neither vocal nor auditory pathologies were found in the participants. Vowels produced by the participants were registered in isolation and they were analyzed using the software PRAAT. In general, the comparison shows that women from Santiago produce higher frequency than men in the analyzed formants (F0, F2, F3 y F4), except in F1. It was also observed that women and men from Santiago show a higher F0 formant than speakers from Rio de la Plata. Finally, no differences were found between speakers from Santiago and speakers from Concepción. In each comparison, a detailed description of the vowel formants is also presented. <!–EndFragment–>